2020
DOI: 10.3390/su12020662
|View full text |Cite
|
Sign up to set email alerts
|

An Econophysics Study of the S&P Global Clean Energy Index

Abstract: The study of how financial markets behave continues to be interesting. The existence of more and more data and the development of statistical techniques are some reasons for the increase in research in finance. However, the difficulty in understanding some markets’ behavior is a continuous challenge. In this context, a new research area called Econophysics has emerged, which is constantly increasing in size. We propose in this work to use methodologies related to Econophysics to analyze one stock index compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Reference [15] applied econophysics methodology to analyze one stock index that consists of firms producing clean energy (S&P Global Clean Energy Index). Besides, they compare it with New York Stock Exchange (NYSE) as a stock market benchmark and the price of crude oil.…”
Section: Prediction Of Developed and Developing Indices Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [15] applied econophysics methodology to analyze one stock index that consists of firms producing clean energy (S&P Global Clean Energy Index). Besides, they compare it with New York Stock Exchange (NYSE) as a stock market benchmark and the price of crude oil.…”
Section: Prediction Of Developed and Developing Indices Usingmentioning
confidence: 99%
“…Many researchers have studied the prediction of stock markets using different macroeconomic factors and feature issues [14][15][16]. However, few researchers tried to predict the performance of stock markets through the integration between different international and national markets' indices [10,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition [ 50 ], found unidirectional connectedness from the implied volatility indices to the clean energy stocks. Then again [ 51 ], utilized the quantile regression method and showed decreasing dependence of clean energy indices on oil returns [ 52 ]. used an Econophysics-based DFA approach to study the behavior of three varied indices including the S&P clean energy index.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Tissaoui and Azibi [36] studied the predictability of Tadawul index and international indices and found that US volatility risk indices are dominant in forecasting the Saudi stock exchange. Moreover, researchers investigated the relationship between international indices and different variables, including the clean energy index [49] and skew phenomenon [50].…”
Section: Tadawul Index (Tasi) and International Indicesmentioning
confidence: 99%